2023
DOI: 10.1038/s41392-022-01304-4
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral microbiota: roles in cancer initiation, development and therapeutic efficacy

Abstract: Microorganisms, including bacteria, viruses, fungi, and other eukaryotes, play critical roles in human health. An altered microbiome can be associated with complex diseases. Intratumoral microbial components are found in multiple tumor tissues and are closely correlated with cancer initiation and development and therapy efficacy. The intratumoral microbiota may contribute to promotion of the initiation and progression of cancers by DNA mutations, activating carcinogenic pathways, promoting chronic inflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
78
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(101 citation statements)
references
References 252 publications
(448 reference statements)
0
78
0
Order By: Relevance
“…Intratumoral microbial components are closely associated with cancer initiation and development and affect anti-cancer approaches' therapeutic potential (20)(21)(22)(23). Here, unbiased genomic analyses revealed an enrichment of the genus Escherichia-Shigella and the specie Escherichia coli increasing in relapse RCC patients and we showed that the colonization by CoPEC is an unfavorable prognostic factor in RCC.…”
Section: Discussionmentioning
confidence: 71%
“…Intratumoral microbial components are closely associated with cancer initiation and development and affect anti-cancer approaches' therapeutic potential (20)(21)(22)(23). Here, unbiased genomic analyses revealed an enrichment of the genus Escherichia-Shigella and the specie Escherichia coli increasing in relapse RCC patients and we showed that the colonization by CoPEC is an unfavorable prognostic factor in RCC.…”
Section: Discussionmentioning
confidence: 71%
“…On the one hand, the intra-tumoral bacteria promote antitumour immunity and therapeutic efficacy through mechanisms such as intra-tumoral microbiota-induced antigen presenting T and NK cell activation, TLS production, and STING signalling activation. 88 Kalaora et al proved that patients with Clostridium, Pseudoxanthomonas, Saccharopolyspora and Streptomyces in tumour tissues showed better ICI response and longer survival, as bacteria-derived peptides are distinct from their counterparts and are more likely to elicit T cell responses. 89 Trimethylamine oxide (TMAO), which is generated by Clostridiales, could enhance immunotherapy efficacy via promoting the CD8 + T cell activation and M1 macrophage infiltration and improving anti-PD-1 therapeutic response.…”
Section: Synergistic Immunotherapeutic Delivery Systemsmentioning
confidence: 99%
“…12 Intra-tumoral bacteria like S. aureus could enhance immunosuppression by adjusting Tregs in the tumour immune microenvironment to influence the liver and prostate cancer development. 88 Commensal fungi can decrease T-cell numbers via binding to Dectin-1 and then inhibit the immunotherapeutic efficiency after radiotherapy. 95 These above studies reveal that intra-tumoral bacterial elimination can be a great potential way to enhance the efficacy of immunotherapy.…”
Section: Synergistic Immunotherapeutic Delivery Systemsmentioning
confidence: 99%
“…This 'intratumoral microbiota' can refer to bacterial infiltrates found in the extracellular matrix or within the cellular components of the tumour such as cancer, immune and stromal cells [2]. It is now widely appreciated that intratumoral bacteria can have direct and indirect effects on tumours or the tumour microenvironment (TME) [3,4]. The presence of specific intratumoral bacteria has been reported to influence multiple features of tumour biology, including treatment efficacy, local immune composition and activity and promoting tumour metastasis [5,6].…”
Section: Introductionmentioning
confidence: 99%